IN VITRO INVESTIGATION OF PROBIOTIC PROPERTIES NEW STRAINS OF LACTIC ACID BACTERIA VALUABLE FOR AQUACULTURE (Experimental biology, 2021)
One of the key points of new paradigm in addressing aquaculture biosafety risks is to enhance disease prevention through responsible fish farming, including reducing antimicrobial resistance in aquaculture and the use of suitable alternatives to antimicrobials, such as probiotics. In this regard, research aimed at the development and implementation of new, effective probiotics for aquaculture based on safe microorganisms capable of preventing and treating fish diseases becomes relevant. The purpose of this scientific investigation was to search and study in vitro the properties of new active strains of lactic acid bacteria for the development of domestic probiotic preparation that increases the resistance and productivity of valuable fish species in aquaculture. The scientific and practical significance of the work is associated with obtaining new knowledge about the tolerance of various species and strains of lactic acid bacteria to adverse environmental factors that model some conditions of the gastrointestinal tract of valuable fish species. In result of this study, a collection of new active strains of lactic acid bacteria resistant to bile, phenol, salt, low pH values ​ ​ and capable of surviving in the gastrointestinal tract of fish, as well as strong antagonists capable of restraining the growth of pathogens causing fish diseases was created. This collection will serve as the basis for the development of a new effective domestic probiotic for aquaculture.
Keywords: lactic acid bacteria; resistance; antagonist; probiotic; aquaculture